INTERNATIONAL MARKET FOR BRAZILIAN BEEF: AN ANALYSIS OF THE CONCENTRATION INDICES OF EXPORTS FROM 2000 TO 2011 - Sanguinet, Eduardo Rodrigues; Lorenzoni, Rodrigo Klein; Pelegrini, Tatiane; Dörr, Andréa Cristina; Fruet, Ana Paula Burin; Klinger, Ana Carolina Kohlrausch (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708789 The study evaluated the export trade of Brazilian beef and to this end we conducted a sectoral analysis to diagnose the factors that make Brazil a major exporter of the product. Ascertained the indexes of market concentration and consumer concurrently measures the evolution of the volume of imports of the 10 largest buyers (from data ABIEC) Brazilian beef in the period from 2000 to 2011. It was found that Brazil has a potential for livestock due to comparative advantages such as abundant land and favorable climatic conditions and that there were major inward investment to the sector. This fact confirms the increasing volume of Brazilian beef exported in recent years. By studying the levels of concentration, it was found that the period of analysis, few countries participated materially in trade of beef from Brazil. We conclude that there are fluctuations in the volumes that each country imports every year, however the group of countries with the highest significance for Brazilian beef exports remain constant and represented 64% of total exports in 2011.